Timarión acerca del vello: tres tipos - Troca Pereira, Reina Marisol (Revista de Estudios Clásicos, 2024)
This article consists of two sections. The first delimits and contextualizes the topos in question, regarding hairiness in literature. The second presents a reflection on the meanings that include the capillary appearance of three figures from the anonymous Byzantine opusculum of the XII century written in ancient Greek, Timarion. In the case of a historical period convulsed in sociocultural, political, and religious terms, literary fiction in a syncretism of elements from classical Antiquity / paganism reinvented and adapted, mutatis mutandis, in the Judeo-Christian paradigm is a necessary mask to transmit messages of Lucian nature regarding multidimensional criticism with a playful tone. The three hair domains analyzed (capillary, mandibular, anal) constitute an enigma that, after filtration, reveals multiple purposes of relevance to the Byzantine context.